Effect of Deformation on Topological Properties of Cobalt Monosilicide - Sergey Nikolaev; Dmitry Pshenay-Severin; Yuri Ivanov; Alexander Burkov (Crystals, 2021)
Recently, it was shown that materials with certain crystal structures can exhibit multifold band crossings with large topological charges. CoSi is one such material that belongs to non-centrosymmetric space group P2<semantics>1</semantics>3 (#198) and posseses multifold band crossing points with a topological charge of 4. The change of crystal symmetry, e.g., by means of external stress, can lift the degeneracy and change its topological properties. In the present work, the influence of uniaxial deformation on the band structure and topological properties of CoSi is investigated on the base of ab initio calculations. The <semantics>k·p</semantics> Hamiltonian taking into account deformation is constructed on the base of symmetry consideration near the <semantics>Γ</semantics> and R points both with and without spin-orbit coupling. The transformation of multifold band crossings into nodes of other types with different topological charges, their shift both in energy and in reciprocal space and the tilt of dispersion around nodes are studied in detail depending on the direction of uniaxial deformation.